Investigation on anonymous email in online social networking / Fatma Husna M Mazlin - M Mazlin, Fatma Husna (2016)
Anonymous email is mostly hassle the email user because they do not know where the email comes from. Besides, anonymous email usually related with cyber crime like banking fraud, identity theft and cyber bullying. The forensic investigators or analysts need to know the source of the email before they proceed for other processes of the investigation. The forensic analysts should have to analyze the anonymous email to find the evidence that related with the cyber crime. Process of analyze the anonymous email; the forensic analysts should use a tool that can trace the source of the anonymous email. IP address location tracker system is a tool that can trace the location of anonymous email based on the IP address of the anonymous email. The information that will be received after tracing the anonymous email are information of country name, region name, city, longitude, latitude, country code and postal code of the IP address. At the end of the project, this IP address location tracker system expected to assist the forensic analysts to find the evidence of digital forensic for anonymous email.